Degradation of water quality caused by typhoon passage: a case study of the Zhejiang coastal waters in 2019 - Cao, Tong; Zhou, Feng; Tian, Di; Meng, Qicheng; Ma, Xiao; Wang, Bin; Zhang, Qianjiang; Xuan, Jiliang; Chen, Jianfang; Huang, Daji (Frontiers in Marine Science, 2024)
The degradation of coastal seawater quality off the Changjiang Estuary and adjacent waters is typically associated with monsoon wind, ocean currents and inputs of terrestrial pollutants. Using a coupled physical-biogeochemical model with Eulerian tracers, this study suggests that, in addition to these factors, the passage of typhoons may be also important in driving short-term fluctuations in coastal water quality.Typhoons Lingling and Tapah (2019) significantly enhanced the southward transport of pollutants from the Changjiang, leading to a sudden and noteworthy degradation of water quality in the Zhejiang coastal region during early autumn, despite no considerable change in monsoon pattern or river discharge compared to normal years.As Lingling and Tapah successively passed through the East China Sea in September, the average nitrate concentration in the Zhejiang coastal waters rose by 77%, and the percentage of heavily polluted water increased by 28%. Our numerical experiments showed that the impacts caused by Lingling and Tapah on nitrate levels in these waters lasted for approximately 34 and 23 days, respectively. These results indicate that typhoons play a crucial role in regulating the transport of pollutants in coastal waters, with significant sub-seasonal effects on the marine biogeochemical environment.